Bacteria in a wood fungal disease: characterization of bacterial communities in wood tissues of esca-foliar symptomatic and asymptomatic grapevines - Bruez, Emilie; Haidar, Rana; Alou, Maryam T.; Vallance, Jessica; Bertsch, Christophe; Mazet, Flore; Fermaud, Marc; Deschamps, Alain; Guerin-Dubrana, Lucia; Compant, Stéphane; Rey, Patrice (Frontiers in Microbiology, 2015)
Esca is a grapevine trunk disease (GTD) associated with different pathogenic fungi inhabiting the woody tissues. Bacteria can also be found in such tissues and they may interact with these fungal colonizers. Although such types of microbial interaction have been observed for wood diseases in many trees, this has never been studied for grapevine. In this study, the bacterial microflora of different vine status (esca-symptomatic and asymptomatic), different anatomical part (trunk and cordon) and different type of tissues (necrotic or not) have been studied. Based on Single Strand Conformation Polymorphism (SSCP) analyses, data showed that (i) specific complexes of bacterial microflora colonize the wood of both necrotic and non-necrotic tissues of esca-foliar symptomatic and asymptomatic vines, and also that (ii) depending on the anatomical part of the plant, cordon or trunk, differences could be observed between the bacterial communities. Such differences were also revealed through the Community-Level Physiological Profiling (CLPP) with Biolog Ecoplates™. Two hundred seventeen bacterial strains were also isolated from plants samples and then assigned to bacterial species based on the 16S rRNA genes. Although Bacillus spp. and Pantoea agglomerans were the two most commonly isolated species from all kinds of tissues, various other taxa were also isolated. Inoculation of vine cuttings with 14 different bacterial species, and one GTD fungus, Neofusicoccum parvum, showed no impact of these bacteria on the size of the wood necroses caused by N. parvum. This study showed, therefore, that bacterial communities differ according to the anatomical part (trunk or cordon) and/or the type of tissue (necrotic or non necrotic) of wood of grapevine plants showing external symptoms of esca disease. However, research into bacteria having a role in GTD development needs further studies.